Editorial - Martínez Martínez, F; Faus Dáder, MJ; Ruiz López, MD (Ars Pharmaceutica (Internet), 2011)
Ars Pharmaceutica is a multidisciplinary scientific journal which focuses on all aspects of pharmaceutical science. It was the first journal of its type in Spain, and has been published by the Faculty of Pharmacy of the University of Granada every year for the past 51 years. During this time, it has evolved in the same way as most scientific journals, and is now no longer only printed in paper format, but is also available free of charge via the Internet. This means that more and more researchers from around the world can access the journal. And they have done so, as proven by the high number of website hits and researchers’ growing interest in having their work published in the journal. Another reason why the number of papers received over the last year has increased is that the journal now accepts papers in both Spanish and English. The journal is currently indexed in the following databases: Chemical Abstracts; ICYT (CSIC); EMBASE/Excerpta Médica; International Pharmaceutical Abstracts (IPA); Indice Bibliográfico Español en Ciencias de la Salud (IBECS); Biological Abstracts; and Life Sciences Collection. We are working to have the journal included in more databases in the future.The current issue, number 52, is the first of a new era, for which we, the editorial team at Ars Pharmaceutica, have set ourselves two priority objectives: to produce a top-quality journal, and to achieve maximum exposure amongst the scientific and pharmaceutical community.We have therefore designed and developed a new website. The different categories of papers suitable for publication have been clearly defined. An electronic submission system has been developed to make it easier for authors to submit their papers via our website. We now have more human and financial resources, and these have allowed us to produce the journal in electronic format, available free of charge to all the scientists and professionals who want to read it.In this new era for the journal, the publication and editorial guidelines will be adapted so that they come into line with international requirements for scientific publications. We would therefore like to remind authors to check that their papers meet the requirements stipulated in the Guide for authors before they submit them to us. Ars Pharmaceutica uses a peer review system so that each paper is reviewed by experts in the research focus of each study and the methodologies used.Our second aim is to increase the readership of Ars Pharmaceutica and encourage authors to submit their papers to the journal. To do this, we will make the publication available to public and private research bodies and scientific and professional associations. We would therefore like to take this opportunity to invite all authors to send their contributions to the different sections of the journal.We cannot sign off without thanking the people whose hard work made all of this possible back in the 1960s, Professors Cabo and Suñé. If it were not for their enthusiasm and determination to create and maintain this journal, with so little money and hardly any external help, we would not be here today, pouring all our renewed energy into what we believe could become a key tool for the dissemination of scientific knowledge in the field of pharmacy.